2015
DOI: 10.1111/iju.12750
|View full text |Cite
|
Sign up to set email alerts
|

Prostate‐specific antigen‐based prostate cancer screening: Past and future

Abstract: Prostate-specific antigen-based prostate cancer screening remains a controversial topic. Up to now, there is worldwide consensus on the statement that the harms of populationbased screening, mainly as a result of overdiagnosis (the detection of clinically insignificant tumors that would have never caused any symptoms), outweigh the benefits. However, worldwide opportunistic screening takes place on a wide scale. The European Randomized Study of Screening for Prostate Cancer showed a reduction in prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 113 publications
0
67
0
4
Order By: Relevance
“…Hayes and Barry recently reviewed randomized trials and modeling studies of screening for prostate cancer with the PSA test and found that two major trials have examined the role of PSA in screening for prostate cancer [5]. The European Randomized Study of Screening for Prostate Cancer (ERSPC) found a reduction in prostate cancer mortality using PSA testing [6,7]. The Prostate, Lung, Colorectal and Ovarian (PLCO) screening trial did not show a prostate cancerspecific mortality benefit with PSA screening [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hayes and Barry recently reviewed randomized trials and modeling studies of screening for prostate cancer with the PSA test and found that two major trials have examined the role of PSA in screening for prostate cancer [5]. The European Randomized Study of Screening for Prostate Cancer (ERSPC) found a reduction in prostate cancer mortality using PSA testing [6,7]. The Prostate, Lung, Colorectal and Ovarian (PLCO) screening trial did not show a prostate cancerspecific mortality benefit with PSA screening [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, more than half of those patients diagnosed by case finding belonged to intermediateor higher-risk groups for which active treatment was recommended. 6,7 One of the concerns is the risk of overdiagnosis and overtreatment of low-risk cancer that may result in more potential harm than benefit to patients. [8][9][10] There are many types of prostate cancer screening approaches.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the well-known Merenstein case from 1999, a general practice resident saw a >50-year-old male patient for a checkup. 2 In accordance with guidelines, prostate-specific antigen (PSA) test risks and benefits were discussed, the patient declined to have it done, and the process was formally documented.…”
mentioning
confidence: 99%